Damp housing, gas stoves, and the burden of childhood asthma in Australia. Issue 7 (16th April 2018) - Knibbs, Luke D; Woldeyohannes, Solomon; Marks, Guy B; Cowie, Christine T
Abstract: Objective: To determine the proportion of the national childhood asthma burden associated with exposure to dampness and gas stoves in Australian homes. Design: Comparative risk assessment modelling study. Setting, participants: Australian children aged 14 years or less, 2011. Main outcome measures: The population attributable fractions (PAFs) and number of disability‐adjusted life years (DALYs) for childhood asthma associated with exposure to damp housing and gas stoves. Results: 26.1% of Australian homes have dampness problems and 38.2% have natural gas as the main energy source for cooktop stoves. The PAF for childhood asthma attributable to damp housing was 7.9% (95% CI, 3.2–12.6%), causing 1760 disability‐adjusted life years (DALYs; 95% CI, 416–3104 DALYs), or 42 DALYs/100 000 children. The PAF associated with gas stoves was 12.3% (95% CI, 8.9–15.8%), corresponding to 2756 DALYs (95% CI, 1271–4242), or 67 DALYs/100 000 children. If all homes with gas stoves were fitted with high efficiency range hoods to vent gas combustion products outdoors, the PAF and burden estimates were reduced to 3.4% (95% CI, 2.2–4.6%) and 761 DALYs (95% CI, 322–1199). Conclusions: Exposure to damp housing and gas stoves is common in Australia, and is associated with a considerable proportion of the childhood asthma burden. Strategies for reducing exposure to indoor dampness and gas combustion products should be communicated to parents of children with or at risk of asthma.